2017
DOI: 10.1007/jhep01(2017)007
|View full text |Cite|
|
Sign up to set email alerts
|

The muon magnetic moment in the 2HDM: complete two-loop result

Abstract: Abstract:We study the 2HDM contribution to the muon anomalous magnetic moment a µ and present the complete two-loop result, particularly for the bosonic contribution. We focus on the Aligned 2HDM, which has general Yukawa couplings and contains the type I, II, X, Y models as special cases. The result is expressed with physical parameters: three Higgs boson masses, Yukawa couplings, two mixing angles, and one quartic potential parameter. We show that the result can be split into several parts, each of which has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 121 publications
(173 reference statements)
0
79
0
Order By: Relevance
“…There are caveats in our reasoning which are worth pointing out: There are two-loop diagrams which also yield sizable contributions for some regions of the parameter space involving quarks and gauge bosons, as already pointed out in [354][355][356] and discussed further in [181,[357][358][359] which may affect our results;…”
Section: Resultsmentioning
confidence: 81%
“…There are caveats in our reasoning which are worth pointing out: There are two-loop diagrams which also yield sizable contributions for some regions of the parameter space involving quarks and gauge bosons, as already pointed out in [354][355][356] and discussed further in [181,[357][358][359] which may affect our results;…”
Section: Resultsmentioning
confidence: 81%
“…[22][23][24][25][26][27] studied the so-called type X (or leptonspecific) model, and the authors of Refs. [28][29][30] the more general (flavor-)aligned model [31,32]. In all these cases it was shown that a light pseudoscalar A boson with large couplings to leptons is viable and could explain Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [22][23][24][25][26][27][28][29][30] and our later considerations show that a μ can be promisingly large for small M A and large ζ l and ζ u , so we focus on this scenario. Our study can be regarded as a generalization of Refs.…”
Section: Constraintsmentioning
confidence: 99%
See 2 more Smart Citations